Existência de solução para problemas elípticos não-locais via teoria de bifurcação - Lima, Romildo Nascimento de (2016)
In this work, we aim to prove the existence of positive solution for some nonlocal elliptic problems via bifurcation theory, more precisely by the Global Bifurcation Theorem due to Rabinowitz, where such problems are related to modeling the behavior of specie in a given environment.